Synthesis and Characterization of Composite Copper – Iron Nanoparticles from Copper Tailings using Sodium Borohydride as Reductant - Okpala-Chinonso, A. N.; Moronkola, B. A.; Alegbe, M. J. (European Journal of Applied Sciences, 2026)
The pollution caused by mine tailing, a leftover after excavating the useful mineral resources is often rich in metal ores that can be used as reagent to synthesize bimetallic or composite copper–iron nanoparticles (Cu–Fe NPs). The aim of this research is to synthesize and characterize composite Cu–Fe NPs synthesized from copper tailings. Experimental approach: Pulverized copper tailing (PCT) particles was digested and used as precursor copper reagent material with reagent iron salt solution to form Cu–Fe solution which was subjected to chemical reduction method. The synthesized composite Cu–Fe NPs was characterized using analytical techniques such as X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), etc. Results: The synthesized Cu–Fe NPs was optimized and characterized using 10 %, 20 %, 30 %, and 40 % of Fe content with the copper tailing solution. XRD showed well-defined crystalline phases corresponding to Cu and Fe oxides with crystallite sizes for 10 %, 20 %, 30 %, and 40 % of Fe to be 10 nm, 6 nm, 8 nm, and 8 nm respectively which varied slightly with the iron content which indicated that Fe incorporation influenced crystal growth and structural properties. SEM images revealed agglomeration, porous, and irregular particle structures across all the samples, while TEM confirmed predominantly spherical morphology with particle sizes of 10 %, 20 %, 30 % and 40 % Fe composition to be 7.2 nm, 3.2 nm, 5.4 nm and 5.3 nm respectively. FTIR identified O–H, CO2, C=O, etc. XRF confirmed copper and iron as the predominant elements in the Cu–Fe matrix. The optimization study revealed the 20 % Fe incorporation was the preferred formulation for the synthesis of Cu–Fe NPs. Conclusion: A suitable quality of bimetallic Cu–Fe NPs was synthesized from the copper waste material.